2007
DOI: 10.1134/s0006297907020071
|View full text |Cite
|
Sign up to set email alerts
|

A system for heterologous expression and isolation of Escherichia coli RNA polymerase and its components

Abstract: A set of plasmid vectors for expression of all major Escherichia coli RNA polymerase subunits as fusion proteins with intein- and chitin-binding domains, allowing protein purification in accordance with IMPACT technology, was constructed. It is demonstrated that the fusion subunits alpha, beta or beta' in conjunction with the natural subunits alpha, beta, beta', and sigma can participate in RNA polymerase assembly in vivo, providing affinity-based isolation of the enzyme. Functional activity of the enzyme prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Furthermore, it was confirmed that this method is compatible with PEG precipitation to remove most nonspecifically bound polynucleotides. Thus this method provides a simple, economical alternative to previously reported single‐step RNAP purification methods involving immunoaffinity chromatography11 or the intein‐based IMPACT‐CN chromatography system 12, 13…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, it was confirmed that this method is compatible with PEG precipitation to remove most nonspecifically bound polynucleotides. Thus this method provides a simple, economical alternative to previously reported single‐step RNAP purification methods involving immunoaffinity chromatography11 or the intein‐based IMPACT‐CN chromatography system 12, 13…”
Section: Discussionmentioning
confidence: 93%
“…Among these is the potential for dissociation of the target complexes during elution from the affinity matrix, and unexpected nonspecific cleavage within the target protein by protease during protease‐mediated affinity tag removal. Although new methods based on gentle immunoaffinity,11 and self‐cleaving chitin‐binding tags have been successfully used to purify protein complexes, including Escherichia coli RNA polymerase (RNAP),12, 13 they still rely on expensive chromatographic methods.…”
Section: Introductionmentioning
confidence: 99%